2014
DOI: 10.1002/jsfa.6722
|View full text |Cite
|
Sign up to set email alerts
|

Beetroot (Beta vulgaris L.) and naturally fermented beetroot juices from organic and conventional production: metabolomics, antioxidant levels and anticancer activity

Abstract: The obtained results indicate that ORG- and CONV-produced beetroots and fermented beetroot juices have different chemical properties and different impacts on cancer cells. It is necessary to continue research on this topic in order to confirm and understand the achieved results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
73
2
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 120 publications
(87 citation statements)
references
References 47 publications
(75 reference statements)
8
73
2
4
Order By: Relevance
“…The identified concentrations were in a range reported in previously published studies (Czyżowska et al, 2006;Szopińska and Gawęda, 2013;Kazimierczak et al, 2014). Higher concentrations of betalains were found in pure beetroot juices when compared to juices combined with other components (apple, lemon).…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…The identified concentrations were in a range reported in previously published studies (Czyżowska et al, 2006;Szopińska and Gawęda, 2013;Kazimierczak et al, 2014). Higher concentrations of betalains were found in pure beetroot juices when compared to juices combined with other components (apple, lemon).…”
Section: Resultssupporting
confidence: 74%
“…This supports many authors findings showing higher contents of vitamin C in organically compared to the conventionally cultivated fruit and vegetables (Brandt et al, 2011) and can be explained by the nitrogen fertilization strategy used in conventional agriculture -increased fertilization tends to reduce the contents of ascorbic acid and other carboncontaining chemical compounds in plants (Stefanelli et al, 2010). The same tendency in terms of vitamin C content was described by Kazimierczak et al (2014) -fermented beetroot juices from organic production were found to contain significantly more vitamin C than the conventional ones. However, in the cited study no effect of the production system (organic/conventional) on the content of organic acids in pure fermented beetroot juices has been identified.…”
Section: Vitamin C and Organic Acidssupporting
confidence: 87%
See 2 more Smart Citations
“…Their levels are dependent on genetic traits, climatic and cultivation conditions, as well as the size and parts of the root. Apart from betalain pigments red beets contain small amounts of hydroxycinnamic acids such as gallic, syringic and caff eic acids, as well as fl avonoids (Kazimierczak et al, 2014), and triterpene saponins, which constitute a numerous group of compounds with a highly diverse chemical structure, being O-glycoside derivatives of 4 diff erent aglycones, i.e. oleanolic acid, hederagenin, akebonoic acid and gipsogenin, to which atypical substituents may be attached, e.g.…”
Section: Introductionmentioning
confidence: 99%